2012
DOI: 10.1094/php-2012-1214-01-rs
|View full text |Cite
|
Sign up to set email alerts
|

Sunflower Diseases Remain Rare in California Seed Production Fields Compared to North Dakota

Abstract: The majority of United States sunflower production is in seven Midwestern states, but hybrid planting seed is almost exclusively produced in California. Due to the lack of summer rains and furrow irrigation, California-produced seed is relatively disease free and thus it regularly meets phytosanitary restrictions imposed by many countries. For the 15-year period from 1997 to 2011, 7231 seed fields in northern California were inspected and samples processed at the state diagnostic laboratory (California Departm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…For example, sunflower hybrid planting seed is almost exclusively produced in California. Due to the lack of summer rains and furrow irrigation, California-produced seed is relatively disease free, and thus, it regularly meets phytosanitary restrictions imposed by many countries (Gulya et al 2012). Fields should be selected such that these are at least 500 m away from a field on which sunflower had been grown the previous year (Jocic ' et al 2012).…”
Section: Cultural Controlmentioning
confidence: 99%
“…For example, sunflower hybrid planting seed is almost exclusively produced in California. Due to the lack of summer rains and furrow irrigation, California-produced seed is relatively disease free, and thus, it regularly meets phytosanitary restrictions imposed by many countries (Gulya et al 2012). Fields should be selected such that these are at least 500 m away from a field on which sunflower had been grown the previous year (Jocic ' et al 2012).…”
Section: Cultural Controlmentioning
confidence: 99%
“…Fortunately, these diseases are very rare in California due to our hot, dry summers. In a 15-year study by Gulya et al (2012), only three quarantine-type diseases were found in sunflower in California, including rust in 4% of fields, Sclerotinia rot in 2.6% of fields, and downy mildew in 0.4% of fields. Each importing country has different pathogens that are excluded.…”
Section: Diseasesmentioning
confidence: 99%